Investigating Oral Communication Strategy Use Qualitatively: Risks of Obtaining Inaccurate Data. - Asmaa AlSaqqaf; Siti Jamilah Bidin; Ahmad Affendi Shabdin; Wardatul Akmam Din; Suyansah Swanto (2016)
Oral communication strategy (OCS) literature reveals that the vast majority of the OCS research has adopted qualitative approaches to identify the OCSs used by second language (L2) speakers. The problem in investigating the OCSs through qualitative techniques lies in the fact that it is highly likely for participants, when performing the qualitative tasks, not to employ all the OCSs they actually utilize in reality and have in their own OCS repertoire. It is argued that those participants could be aware of those OCSs if asked consciously by answering a questionnaire. Hence, it could be hypothesized that many OCSs examined in the past research failed to be identified because of the obvious lack of another technique that could have elicited several OCSs that might have been existent in the participants repertoire. This paper sheds light on this problematic issue that may many OCS researchers may not be aware of. It also attempts to suggest some recommendations that may hopefully help to address this dilemma.